PENGARUH KOMPETENSI, INDEPENDENSI DAN PENGALAMAN AUDIT APARAT PENGAWASAN INTERN PEMERINTAH TERHADAP KUALITAS AUDIT INTERNAL DENGAN ETIKA SEBAGAI VARIABEL MODERASI PADA INSPEKTORAT JENDERAL DI TENTARA NASIONAL INDONESIA - Sri Sukesi (Jurnal Magister Akuntansi Trisakti, 2019)
This study aims to determine the effect of competency, independence, audit experience with ethics as a moderating variable on the quality of internal audit both simultaneously and partially at the Inspectorate General in the Indonesian Armed Forces. The method used in this study is a causal research method that aims to determine the causal relationship of the independent variables, namely competence, independence and audit experience with the dependent variable, namely audit quality with ethical moderation variables.The study population was 139 with a sample of 105 people determined using purposive sampling technique. The technique of collecting data using a questionnaire. Data instrument testing is done by validity and reliability testing, while the data analysis is correlation, determination, moderation regression and hypothesis testingBased on the results of hypothesis testing, simultaneously competency, independence, and audit experience in ethical moderation have a positive effect on the quality of internal audit. Partially from the competency and experience have a positive effect on the quality of internal audit, but he independence variable does not affect the quality of internal audit. Ethics as a moderating variable can strengthen the influence of audit experience variables on internal audit quality,and Ethics as a moderating variable cannot strengthen the influence of competence and independence on the quality of internal audit.